2010
DOI: 10.1016/j.amjopharm.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of hallucinations and psychosis in Parkinson's disease

Abstract: Abstract:BACKGROUND: Hallucinations and psychosis are common in patients with Parkinson's disease (PD), with reported prevalences of up to 48% and 80%, respectively. However, few randomized, double-blind, placebo-controlled trials evaluating the treatment options have appeared in the literature. The studies that have been published were complicated by lack of agreement on the diagnosis of psychosis in PD, poor completion rates, mixed populations that included dementia, and other issues. Several reviews, guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 45 publications
(12 reference statements)
0
28
0
1
Order By: Relevance
“…Upon completion of this activity, participants should be able to: [47,48]. Reported efficacy has been variable and specific effects on visual hallucinations have not been reported.…”
Section: Learning Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon completion of this activity, participants should be able to: [47,48]. Reported efficacy has been variable and specific effects on visual hallucinations have not been reported.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…Just about all evidence for pharmacological interventions comes from studies in PD, and LBDs (see Table 2) [48][49][50][51][52][53][54][55][56][57][58] though, even here, primary (or even secondary) outcomes in these trials do not specifically target visual hallucinations and any effect is often conflated with other psychiatric symptoms and behaviors. Thus, there is little evidence to suggest differential treatment responses in different pathologies.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…However, there are inconsistent study data regarding the effectiveness of quetiapine. Although several open label studies reported that quetiapine is effective for treatment of psychosis in patients with PD and two single-blind randomized trials [ 137 ] comparing quetiapine and clozapine reported they were equally effective, only one of fi ve small randomized controlled [ 139 ]. In community studies, quetiapine was reported to have a lower risk of cardiovascular death compared to other atypical agents, with an absence of a dose-response effect in relation to the risk of death [ 140 ].…”
Section: Th Step: Specifi C Managementmentioning
confidence: 94%
“…Although initial clinical manifestations of PD are motor, the progression of the disease is associated with the development of a number of psychiatric symptoms (Hely et al, 2005;Weintraub and Stern, 2005). Psychosis may ultimately occur in more than 40% of patients with PD, and perhaps in as many as 80% (Aarsland et al, 1999;Eng and Welty, 2010;Forsaa et al, 2010). The emergence of these psychotic symptoms is associated with greater functional impairment, increased nursing home placements, and higher rates of morbidity (Goetz and Stebbins, 1993;Marsh et al, 2004).…”
Section: Introductionmentioning
confidence: 97%